AB1242-HPR Fear of Movement Affects Functional Levels and Quality of Life After Total Hip Arthroplasty. (9th June 2015) - Onal, S.; Guney, H.; Sarial, C.; Kinikli, G.I.; Yuksel, I.
Abstract : Background: Though total hip arthroplasty (THA) is a successful procedure for the late stage of hip osteoarthritis, high pain levels and functional impairment are considerable. In addition, THA patients suffer from psychological symptoms such as kinesiophobia/fear of movement. Objectives: The purpose of this study was to determine the fear of movement impact on functional levels and quality of life. Methods: Forty-two patients who underwent unilateral THA were included in the study. Tampa Scale for Kinesiophobia (TSK) was applied to detect fear of movement level. A high value on the TSK indicates a high degree of fear of movement and a score of 37 differentiates between high and low scores. Patients were divided into two groups either to have high scores (Group I; high kinesiophobia, n=22) or low scores (Group II; low kinesiophobia, n=20). Western Ontario and McMaster Osteoarthritis Index (WOMAC) pain, stiffness and activity of daily living questionnaire and Hip Osteoarthritis Outcome Survey-Physical Function Survey (HOOS-PS) were used to determine the functional status. Physical component summary (PCS) and mental component summary (MCS) of Short Form-12 (SF-12) was used to define the quality of life level. Intensity of pain was measured with visual analog scale (VAS). Assessments were applied at least three months after surgery and time after surgery was recorded. Statistical analysis of the data was performed with Mann Whitney-U test. Results: There were no differences in age (p=0.72), BMI (p=0.31), time from surgery (p=0.11), WOMAC pain (p=0.41), WOMAC stiffness (p=0.87), SF-12 MCS (p=0.57)scores between Group I and Group II (Table I).The pain levels (p=0.02), HOOS-PS (p<0.001) WOMAC-ADL and SF-12 PCS (0.02) scores were better in Group II (low kinesiophobia) when compared to Group I (high kinesiophobia). Conclusions: Fear of movement has an adverse effect on pain, functional levels and activity of daily living in THA patients. References: Cheatham SW, Mokha M, Lee M. Postoperative Rehabilitation After Hip Resurfacing: A Systematic Review.J Sport Rehabil. 2015 Jan 22. Peter WF, Dekker J, Tilbury C, Tordoir RL, Verdegaal SH, Onstenk R, Bénard MR, Vehmeijer SB, Fiocco M, Vermeulen HM, van der Linden-van der Zwaag HM, Nelissen RG, VlietVlieland TP. The association between comorbidities and pain, physical function and quality of life following hip and knee arthroplasty. Rheumatol Int. 2015 Jan 14. Disclosure of Interest: None declared